Estudo da influência do fluoreto de cálcio na bioatividade de vidros borato - ALVES, Luana Cristina Feitosa (2017)
Bioactive borate glass has presented superior results then bioactive silicate glasses, when compared its conversion rates in apatite and its potential of bioactivity. In this work, new Borate glasses with the basic 60B2O3 - 4P2O5 - 18Na2O – xCaF2 – (18-xCaO), com x = 0, 5 e 10 % wt were synthesized, and investigated the influence of CaF2 addition on bioactivity of samples in vitro, in a period of 28 days in a simulator of the body fluid (SBF). This bioactivity was investigated by means of X-ray diffraction (DRX), Raman Spectroscopy, FTIR and by the measure of pH. DRX measures, prior to immersion, presented wide bands, evidencing the amorphous structure of glasses. The results of density, thermal analysis, XRD, Raman and FTIR show that the addition of CaF2, until 10 % wt, did not cause significant changes in samples network structure. The thermal stability for all samples was calculated from DSC data and all presented values up to 120°C. The results of pH of SBF solution show increase from for 24 hours, which contributes to the dissolution of the outermost layer of the glass and the precipitation of apatite. In XRD data for 60B sample soaked in SBF for 7 days, there was formation of crystalline peaks, at 26° and 32° (2ϴ), in all measures. These peaks correspond to patterns of hydroxyapatite (HA). The XRD spectra in 60B5CaF and 60B10CaF, soaked in SBF for 7 days, presented peaks in 28°(2ϴ) corresponding to fluorapatite (FA), due to the presence of CaF2 in these glasses. Raman and FTIR measurements confirmed what was measured by XRD, showing characteristic peaks of HA and FA for all the samples. Results show that the prepared samples present potential for being used as biomaterials in biomedical applications, such as orthopedics, dentistry and tissue engineering.